2021
DOI: 10.1039/d1fo02431k
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated polysaccharides from pacific abalone attenuated DSS-induced acute and chronic ulcerative colitis in miceviaregulating intestinal micro-ecology and the NF-κB pathway

Abstract: Due to potential side effects of current drugs in colitis treatment, polysaccharides with anti-inflammatory activity can be considered as an alternative molecule for colitis treatment. Sulfated polysaccharide from pacific abalone...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…It has been demonstrated that the Lachnospiraceae taxa could contribute to the general symptoms of IBS [ 55 , 56 ]. Jia et al [ 57 ] reported that the abundance of Bacteroidaceae increased significantly and Lactobacillaceae decreased significantly in the DSS-treated mice, and our results were consistent with this finding. Recent studies have also found that intestinal dysbacteriosis was the leading cause of infantile diarrhea and Lactobacillaceae could alleviate the severity of diarrhea [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has been demonstrated that the Lachnospiraceae taxa could contribute to the general symptoms of IBS [ 55 , 56 ]. Jia et al [ 57 ] reported that the abundance of Bacteroidaceae increased significantly and Lactobacillaceae decreased significantly in the DSS-treated mice, and our results were consistent with this finding. Recent studies have also found that intestinal dysbacteriosis was the leading cause of infantile diarrhea and Lactobacillaceae could alleviate the severity of diarrhea [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…α- d -Glucan and β- d -glucan from marine fungus Phoma herbarum YS4108 and yeast, respectively, have been proven to ameliorate mice colitis by inhibiting the expression of inflammatory mediators and enhancing the expression of TJ proteins associated with intestinal permeability. Additionally, acidic heteropolysaccharides, such as the sulfated polysaccharide from Pacific abalone, which was composed of Man, Glc, Gal, and GlcA in the molar ratio of 0.9:0.6:16.7:5.2, could attenuate DSS-induced acute and chronic UC in mice via regulating intestinal microecology and the NF-κB pathway . Acidic polysaccharides have a net negative charge and can interact with positively charged amino acids located at the C and N termini of mucin .…”
Section: Protective Effect Of Polysaccharides On Intestinal Barrier F...mentioning
confidence: 99%
“…Additionally, acidic heteropolysaccharides, such as the sulfated polysaccharide from Pacific abalone, which was composed of Man, Glc, Gal, and GlcA in the molar ratio of 0.9:0.6:16.7:5.2, could attenuate DSS-induced acute and chronic UC in mice via regulating intestinal microecology and the NF-κB pathway. 166 Acidic polysaccharides have a net negative charge and can interact with positively charged amino acids located at the C and N termini of mucin. 162 This feature affects mucosal interactions and mucus barrier properties to improve the mucus barrier in colitis mice.…”
Section: ■ Pathogenesis Of Intestinal Barrier Injurymentioning
confidence: 99%
“…Polysaccharides from S. baicalensis Georgi ameliorated colitis via suppression of the NF-κB signaling pathway [128] while increasing the levels of Firmicutes, Bifidobacterium, Lactobacillus, and Roseburia and reducing the levels of Bacteroides, Proteobacteria, and Staphylococcus [65]. Similarly, Pacific abalone polysaccharides could inhibit the activation of the NF-κB signaling pathway, increase Muribaculaceae and Lachnospiraceae abundance, and decrease Bacteroidaceae, Prevotellaceae, and Rickenellaceae abundance [129].…”
Section: Effect On Intestinal Immunity and Inflammatory Responsesmentioning
confidence: 99%